2013
DOI: 10.1177/0363546513498988
|View full text |Cite
|
Sign up to set email alerts
|

The Microvascular Volume of the Achilles Tendon Is Increased in Patients With Tendinopathy at Rest and After a 1-Hour Treadmill Run

Abstract: This study underlines that tendon flexibility is altered in patients with AT and that CEU is a promising tool to establish the early diagnosis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 55 publications
7
46
1
4
Order By: Relevance
“…This is consistent with other studies that have reported a short-term response in hydration level using off-resonance saturation MRI, 90 tendon volume and intratendinous signal on MRI, 84 and microvascular volume on real-time, harmonic, contrast-enhanced ultrasound 71 in response to load. Of interest is that these studies reported an altered response in tendinopathic tendons.…”
Section: Can Imaging Predict the Onset Of Pain Or Clinical Outcome?supporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with other studies that have reported a short-term response in hydration level using off-resonance saturation MRI, 90 tendon volume and intratendinous signal on MRI, 84 and microvascular volume on real-time, harmonic, contrast-enhanced ultrasound 71 in response to load. Of interest is that these studies reported an altered response in tendinopathic tendons.…”
Section: Can Imaging Predict the Onset Of Pain Or Clinical Outcome?supporting
confidence: 93%
“…Of interest is that these studies reported an altered response in tendinopathic tendons. 39,71,79 These new imaging modalities may provide insight into how tendons respond to load. There is overwhelming evidence that structural disorganization predates the development of symptoms and tendon rupture.…”
Section: Can Imaging Predict the Onset Of Pain Or Clinical Outcome?mentioning
confidence: 99%
“…Several studies have identified vascular hyperplasia in painful tendons and degenerative processes resulting from sports activity [29, 30]. These findings supported the results of clinical studies using color Doppler examination simultaneously with ultrasonography that showed a neovascularization in areas with tendon injury [31, 32]. Normally, avascular tendon tissue becomes hypervascularized during tendinopathy, which supported a key role for VEGF-KDR signals in the pathological angiogenesis in tendinopathy, because VEGF stimulate endothelial cells and vessels to invade hypovascularized tendon areas [12, 13].…”
Section: Discussionsupporting
confidence: 66%
“…While no significant differences in baseline and postexercise D* values were observed, this may have been caused by the large variation of estimated values and potentially only a small change in blood velocity. Unlike in healthy Achilles tendon, a US study of symptomatic tendinopathy patients observed only a 75% increase in Achilles tendon blood volume after treadmill running . It has been hypothesized that high baseline blood flow of tendinopathic tendon may cause dilation of blood vessels at baseline, thus preventing the ability to achieve postexercise peak flux and resulting in delayed recovery.…”
Section: Discussionmentioning
confidence: 99%